Umbilical coiling index as a marker of perinatal outcome: An analytical study at Navodaya Medical College, Raichur - Kumar, Sandeep; Chetty, Sanjeev (Indian Journal of Child Health, 2017)
Objectives: To measure the umbilical coiling index (UCI) postnatally and to study its association with adverse antenatal and perinatal outcome. Materials and Methods: This prospective study was carried out in the department of pediatrics at Navodaya Medical College, Raichur, Karnataka, from June to July 2016. 200 patients who were in active labor irrespective of their parities, who had singleton pregnancies with live babies who were either delivered by vaginal, instrumental, or lower segmental cesarean section were included in the study and multiple pregnancies, malpresentations, previously diagnosed intrauterine device, and elective cesarean section were excluded. UCI was calculated at the time of delivery by dividing the total number of coils by the total umbilical cord length in centimeters. Its association with various maternal and perinatal risk factors was noted. The statistical tests were the Chi-square test and assessed with EPI Info Version 12.0 software and statistically analyzed. Results: The mean UCI was 0.25±0.03. Hypocoiling or UCI 0.37) was found to be associated withpregnancy-induced hypertension, preterm, diabetes mellitus, postpartum hemorrhage, polyhydramnios, NICU admission, abnormal FHR, MSL, and low APGAR at 1 min. Conclusion: Abnormal UCI is associated with several antenatal and perinatal adverse features.